2022
DOI: 10.3201/eid2803.212299
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Convalescent Plasma for Treatment of Severe COVID-19

Abstract: Clinical research is necessary for an effective response to an emerging infectious disease outbreak. However, research efforts are often hastily organised and done using various research tools, with the result that pooling data across studies is challenging. In response to the needs of the rapidly evolving COVID-19 outbreak, the Clinical Characterisation and Management Working Group of the WHO Research and Development Blueprint programme, the International Forum for Acute Care Trialists, and the International … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 56 publications
(60 reference statements)
0
29
0
1
Order By: Relevance
“… Trials that were stopped too early to observe benefit or with inherent design flaws and/or were underpowered such that the likelihood of success was reduced (e.g., C3PO [ 27 ]). Trials in which CCP was used to treat a condition not amenable to antibody intervention, such as hypoxia that is caused by pulmonary inflammation (e.g., COP20 [ 111 ], RBR-7f4mt9f [ 112 ], or REMAP-CAP [ 35 ]). …”
Section: Discussionmentioning
confidence: 99%
“… Trials that were stopped too early to observe benefit or with inherent design flaws and/or were underpowered such that the likelihood of success was reduced (e.g., C3PO [ 27 ]). Trials in which CCP was used to treat a condition not amenable to antibody intervention, such as hypoxia that is caused by pulmonary inflammation (e.g., COP20 [ 111 ], RBR-7f4mt9f [ 112 ], or REMAP-CAP [ 35 ]). …”
Section: Discussionmentioning
confidence: 99%
“…Among all the included studies, 4 studies ( 24 , 28 , 34 , 48 ) were preprinted and 28 studies ( 16 – 18 , 25 27 , 29 33 , 35 – 47 , 49 52 ) were published in peer-reviewed journals. 10 studies ( 24 , 26 , 31 , 38 , 41 , 43 , 44 , 46 , 50 , 51 ) were double-blind RCTs with placebo and 22 studies ( 16 – 18 , 25 , 27 30 , 32 37 , 39 , 40 , 42 , 45 , 47 49 , 52 ) were designed as open-label trials. All trials included patients with confirmed Covid-19 except for the RECOVERY trial ( 35 ), which included both suspected and confirmed COVID-19 patients.…”
Section: Resultsmentioning
confidence: 99%
“…The assessments of risk of bias were shown in Figure 2 . 8 studies ( 26 , 35 , 38 , 41 , 43 , 44 , 46 , 50 ) were regarded as low risk of bias, and 16 studies ( 16 – 18 , 25 , 27 , 29 , 30 , 32 , 37 , 39 , 40 , 42 , 45 , 47 , 49 , 52 ) contained potential performance bias for the open-label design. 4 studies were considered as containing potential bias due to early termination ( 31 , 33 , 36 , 51 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Among 26 phase 2 or 3 CCP trials identified in PubMed between 2020-2022, 18 measured nAb on all units reported (N=2,692 CCP participants) whereas the other eight either did not perform an end-titer assay 20 , reported nAb titer in only a subset of units 19,21 , or did not report nAb titer 3,22-25 (N=7,079 CCP partcipants). Using in-study mortality as the most consistently reported primary or secondary outcome, aggregate risk ratios for death in CCP treated-participants versus no CCP comparator groups in trials reporting incomplete or undefined nAb titer (n=8), median nAb < 1:160 (n=7), 26,27,28,4,29,30,31 or nAb ≥ 1:160 (n=11) 2,4,5,32-39 were 0.99 (0.93-1.04), 1.04 (0.86-1.26), and 0.88 (0.73-1.05), respectively ( supplementary figure 2 ). The median nAb titer in four studies exceeded 1:320, but only one other study reported a median nAb >1:640 in a CCP intervention arm.…”
Section: Discussionmentioning
confidence: 99%